Laparoscopic Management of Tubo-Ovarian Stitch Abscess after Tubal Sterilization - Ghongdemath, Jyoti S (J Gynecol Endosc Surg, 2011)
Tubo-ovarian abscess usually results from ascending infection of the lower genital tract. In few cases, it can occur as a result of direct contamination at the time of tubal sterilization. We describe two rare cases of “tubo-ovarian stitch abscess” after post-partum tubal sterilization and managed successfully by laparoscopy at a tertiary care teaching hospital.